Using songs to develop the listening skill at an intermediate lavel, in an EFL classroom - Samaniego, Magaly; Zúñiga, Mayra
Teaching English as a Foreign Language is a fundamental aspect in education. In order to acquire this important language, we need to master the four skills: listening, speaking, reading and writing. Listening is, however, one of the most important skills to develop when learning a language, since in our daily life, we listen more than what we write, read or speak. We should thus start developing the listening skill in our students intensively. Songs are effective tools to develop the listening skill. Therefore, teachers have to consider songs as a highly motivating teaching resource, since they have the power of enriching and activating our English language classes. Students, especially teenagers, enjoy learning English by means of songs because they are catchy, authentic and make learning easier. The use of songs in EFL classrooms will help students to develop their listening skill, and thus to enhance their communicative abilities. The songs and activities proposed in this monograph can be adapted if teacher requires to do so, or they can be used exactly the way they have been presented.